SIMULATION AND ACQUISITION OF GPS L5 FREQUENCY SIGNAL AND COMPARISON WITH L1 SIGNAL - Latif, K.; Usman, M.; Hanif, A. (The Nucleus, 2014)
Recent advances in GPS modernization efforts include transmission of L5 frequency signals. This paper emphasizes on the implementation of acquisition techniques for GPS L5 and GPS L1 signals. Both signals have been simulated and analysed in a detailed manner to obtain better acquisition results. In this context the signals have been generated, transmitted, received and acquired by suitable algorithms. Simulations were performed using Borland C++ Builder Compiler and MATLAB softwares. Results reveal that L5 signal offers many advantages, including that the acquisition peaks are more accurate, dominant and wider as compared to L1 signal, thus improving GPS system overall performance. Moreover, L5 signals reduce vulnerability to waveform deformation. Noise levels are also comparatively lower than previous signals.